2009
DOI: 10.1021/ol802772s
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Potent Antitumor Agent C11-Deoxypsymberin/irciniastatin A: Total Synthesis and Biology of Advanced Psymberin Analogs

Abstract: Structure-activity relationship (SAR) studies by modification of the unsaturated side chain of potent anticancer marine natural product psymberin/irciniastatin A (1) suggest that substitution at C4 and C5 is important for the cytotoxicity of psymberin, but the terminal double bond is not essential for activity. An aryl group is a good replacement for the olefin. The total synthesis of structurally simplified C11-deoxypsymberin (29) was completed, and its activity is consistently more potent than the natural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…1033 The use of copper-catalysis in the formation of C-N, C-O and C-S bonds including aryl and vinyl substituted derivatives covering a broad spectrum of amines, ethers, and thioethers, in good to excellent yields has been reported. 78,36 It has now been shown that the formation of vinylic C-N and C-O bonds by a Cu-catalytic method 7 is ineffective with the functionalized ethyliodoacrylate substrates, for both phenols and N -heterocycles as nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…1033 The use of copper-catalysis in the formation of C-N, C-O and C-S bonds including aryl and vinyl substituted derivatives covering a broad spectrum of amines, ethers, and thioethers, in good to excellent yields has been reported. 78,36 It has now been shown that the formation of vinylic C-N and C-O bonds by a Cu-catalytic method 7 is ineffective with the functionalized ethyliodoacrylate substrates, for both phenols and N -heterocycles as nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…11b Based on this observation, we synthesized the C11-deoxypsymberin 91 using a similar synthetic sequence as for natural psymberin starting with the preparation of central piece 92 (Scheme 13). 23 than psymberin across all cancer cell lines tested with IC 50 values in the subnanomolar ranges while epimer 91c showed excellent activity against all cell lines tested with IC 50 value in single digit nanomolar ranges (Table 5).…”
Section: Scheme 12mentioning
confidence: 99%
“…Despite a broad range of activities and high levels of potency, compounds from the pedrin family have not been extensively developed for therapeutic purposes. However, recent advances in their syntheses 11–14 and a growing literature into structure activity relationships within this family 15,16 provide a framework for future developments. Furthermore, new insights into the biosynthesis of these interesting metabolites open the possibility of their production in large scale through biotechnological approaches 17,18 as well as the development of new analogs through biosynthesis or semisynthesis 19.…”
Section: Introductionmentioning
confidence: 99%